Quality of Life of Post Stroke Patients: Descriptive Study - Rahayu, Trio Gustin; Setiyani, Solis (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Stroke is the second cause of death after heart disease in the world. It can affect the patients’ life in various aspects such as physical, emotional, psychological, cognitive and social, which can impact on their quality of life. The number of stroke patients at Berkah General Hospital in Pandeglang in the first trimester of 2023 was 290 patients. This study aimed to find out the quality of life of post stroke patients at Pandeglang General Hospital. It was a descriptive study with a total of 40 respondents who were selected by purposive sampling technique. The research location was the neurological clinical room. The study was conducted in May 2023. The respondents filled out the WHO quality of life questionnaire, namely WHOQOL-BREF, which consists of 26 questions. The analysis was used to obtain data distribution on respondent characteristics and patient quality of life. The research results showed the characteristics of the respondents were male (55%), average age 51-60 years (40%), junior high school education (40%) and occupation as housewife (52%). It was found that the best quality of life was found in the social relations domain among other three quality of life domains, namely health, psychological, and environmental domains.